Evaluation of Pediatric Patients with Biliary Tract Dysfunction using Ultrasound Techniques (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Despite advancements in surgical methods and post-transplant care, liver and kidney transplantsstill pose significant risks of complications such as graft rejection, infection, and severe consequences. Thesecomplications may emerge shortly after surgery or several months to years later. Early detection of complicationsin transplant recipients is crucial. Ultrasound (US) is the key technique for visually assessing transplantedorgans and delivering diagnostic information on blood vessel opening and blood flow to organs. This studyaimed to explore the potential of US techniques for evaluating pediatric patients with biliary tract dysfunction.Materials and Methods: The study included 128 children aged 7–14 years, with 100 children in the experimentalgroup and 28 in the control group. The experimental group was divided into two subgroups: Group 1 consisted of57 children with hypokinetic biliary dyskinesia and Group 2 consisted of 43 children with hypermotor dyskinesiaof the biliary tract. Results: In cases of hypokinetic biliary dyskinesia, the motor function indicator significantlydecreased below that of the control group (P < 0.01) and was twice as low as that of the hypermotor type (P < 0.001).In contrast, in group 2, this value exceeded that of the control group (P < 0.01). The study demonstrated thatdynamic US indicators for functional disorders of the gallbladder (GB) have relatively high sensitivity (91%) andspecificity (87%). Conclusion: This study identified variations in biliary tract function during US examinationsin children with different forms of dyskinesia. Alterations in GB function affect the overall performance of thehepatobiliary system in pediatric patients.